Wavelength‐Tunable Micro/Nanolasers. Issue 17 (19th June 2019) - Zhuge, Ming‐Hua; Pan, Caofeng; Zheng, Yazhi; Tang, Jianbin; Ullah, Salman; Ma, Yaoguang; Yang, Qing
Abstract: Micro/nanolasers (MNLs) emit coherent light on the micro/nanoscale. Research on the application of MNLs has progressed rapidly in the past two decades because of their great potential for optoelectronics with compact sizes, low cost, and low energy consumption. Wavelength‐tunable MNLs are essential for a variety of fields including optical communications, solid‐state lighting, and on‐chip wavelength‐division multiplexing. Thus far, tremendous progress is achieved toward the development of wavelength‐tunable MNLs based on bandgap tuning and cavity design. Lasing wavelength is substantially defined by material bandgap, tuned by changing the geometry of the cavity structures, and can also, to some extent, be influenced by operational environment. This review is focused on the intrinsic merits of wavelength‐tunable MNLs, and the recent progress is examined. Bandgap engineering, materials synthesis, cavity structure design, wavelength‐tuning principles, and lasing performance are explored and systematically discussed. Finally, the current research status and perspectives on possible future applications are summarized. Abstract : Wavelength‐tunable micro/nanolasers are essential for a variety of applications including optical communications, solid‐state lighting, and on‐chip wavelength‐division multiplexing. Up to now, tremendous progress is achieved toward the development of wavelength‐tunable micro/nanolasers with increasing performances. In this review, an understanding of the principles along with very recent reports of this promising field is summarized and discussed.